2007
DOI: 10.1177/0269215506070792
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of maximal static strength measurements of the arms in subjects with hemiparesis

Abstract: The maximal strength measurements of the arms in subjects with hemiparesis are reliable. The strength ratios are also reliable and can be used to quantify strength impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 20 publications
(6 reference statements)
3
35
0
3
Order By: Relevance
“…This finding is plausible since handgrip strength was previously found to be a good surrogate measure to characterize overall ipsilateral U/E strength [40, 41] and a strong predictor of functional performance during activities of daily living [42] and of ambulation ability [43]. Moreover, the fact that the MWPT 6 min incorporates frequent stops and starts at high velocity also translates into an increased muscular demand and potential fatigability.…”
Section: Discussionmentioning
confidence: 79%
“…This finding is plausible since handgrip strength was previously found to be a good surrogate measure to characterize overall ipsilateral U/E strength [40, 41] and a strong predictor of functional performance during activities of daily living [42] and of ambulation ability [43]. Moreover, the fact that the MWPT 6 min incorporates frequent stops and starts at high velocity also translates into an increased muscular demand and potential fatigability.…”
Section: Discussionmentioning
confidence: 79%
“…The low variance attributable to test sessions and raters found for the majority of indices in our study (< 5%) suggests that a training of only a few hours (like in this study) may be enough to ensure agreement between physiotherapists for marker placement. In our study, the mean of two trials was used to assess the level of reliability but in practice, one trial could be used (which would save time) since trials had no effect on the test-retest and inter-rater reliability [54][55][56][57][58]. Photograph acquisition is fast and calculation of posture indices can be delayed until later, which is useful for assessing persons with pain or balance disorders, who would not be able to tolerate long evaluations in standing.…”
Section: Discussionmentioning
confidence: 99%
“…Our SEM values are also similar or lower than those found in other reliability studies conducted with subjects with chronic hemiparesis. [8][9][10][11][12] M A N U S C R I P T…”
Section: Relationship Between Grip Strength Measurements and The Motrmentioning
confidence: 99%
“…6,7 Studies have also shown that maximal grip strength measurements are reliable in subjects with hemiparesis. [8][9][10][11][12] However, none of these studies was conducted with this population specifically in acute or sub-acute phases following stroke in spite of the clinical relevance of grip strength measurements during these phases to document the early evolution of upperextremity paralysis or paresis. It could be hypothesized that these measurements are not reliable in the acute or post-acute phase due to fatigue, incoordination or the low range of strength values.…”
Section: Introductionmentioning
confidence: 99%